2021
DOI: 10.3390/met11030381
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Analysis of Experiments on Damage and Fracture Behavior of Differently Preloaded Aluminum Alloy Specimens

Abstract: A large amount of experimental studies have shown significant dependence of strength of ductile metals on stress state and stress history. These effects have to be taken into account in constitutive models and corresponding numerical analysis to be able to predict safety and lifetime of engineering structures in a realistic manner. In this context, the present paper deals with numerical analysis of the influence of the load path on damage and fracture behavior of aluminum alloys. A continuum damage model is di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…to occur [10,39]. In the case of the investigated anisotropic material the failure mode also depends on loading direction with more small sheared voids for loading in RD and more pronounced shear-crack mechanisms with marginal number of initial voids for loading in DD and TD.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…to occur [10,39]. In the case of the investigated anisotropic material the failure mode also depends on loading direction with more small sheared voids for loading in RD and more pronounced shear-crack mechanisms with marginal number of initial voids for loading in DD and TD.…”
Section: Resultsmentioning
confidence: 89%
“…11(c)). In this case in isotropic materials the mixed failure mode with simultaneous growth of voids and formation of micro-shear-cracks is expected to occur [10,39]. In the investigated anisotropic aluminum alloy the damage and fracture mode is also dependent on the F 1 -loading direction with more superimposed void growth for F 1 -loading in RD and more pronounced shear-crack mechanisms for F 1 -loading in DD and TD.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Gerke et al [5] applied the X0-specimen to determine the dependence of non-proportional loading paths on damage evolution and fracture behaviour of an aluminium alloy EN AW 6082 and indicated the significant influence of the strain history on the fracture behaviour. In continuation Brünig et al [6] confirmed these results with the H-specimen. Besides its influence on damage evolution and fracture behaviour the pre-loading history affects remarkably the load-displacement curves, while the IOP Publishing doi:10.1088/1757-899X/1238/1/012023 2 final stresses are almost unaffected.…”
Section: Introductionmentioning
confidence: 57%
“…A recently proposed approach is the use of biaxial specimens [12] made of sheets, in which the ratio of axis loading can be changed in defined ways, and thus the stress states in critical regions of the specimen can be varied sequentially and by superimposed loadings [33][34][35]. This method is characterized by a wide range of possible variations in the individual stress states as well as in the design of non-proportional load paths [36,37].…”
Section: Introductionmentioning
confidence: 99%